Association between Semen Exposure and Incident Bacterial Vaginosis - Maria F. Gallo; Lee Warner; Caroline C. King; Jack D. Sobel; Robert S. Klein; Susan Cu-Uvin; Anne M. Rompalo; Denise J. Jamieson (Hindawi Limited, 2011)
Objective. To identify correlates of incident bacterial vaginosis (BV) diagnosed with Nugent scoring among high-risk women. Study Design. We conducted both cohort and case-crossover analyses, stratified by HIV infection status, based on 871 HIV-infected and 439 HIV-uninfected participants in the HIV Epidemiology Research Study, conducted in 4 US sites in 1993-2000. Results. BV incidence was 21% and 19% among HIV-infected and -uninfected women, respectively. Fewer correlates of BV were found with case-crossover than with cohort design. Reporting frequent coitus (regardless of consistency of condom use) was correlated with BV in cohort analyses but not in case-crossover analyses. The sole correlate of BV in both types of analyses was the detection of spermatozoa on Gram stain, which is a marker of semen exposure. Conclusion. The inconsistent association between condom use and BV in prior studies could be from reporting bias. We found evidence of a relationship between semen exposure and incident BV.